2016
DOI: 10.3847/0004-6256/151/3/82
|View full text |Cite
|
Sign up to set email alerts
|

DETAILED CHEMICAL ABUNDANCES IN THE r-PROCESS-RICH ULTRA-FAINT DWARF GALAXY RETICULUM 2*

Abstract: The ultra-faint dwarf galaxy Reticulum 2 (Ret 2) was recently discovered in images obtained by the Dark Energy Survey. We have observed the four brightest red giants in Ret 2 at high spectral resolution using the Michigan/Magellan Fiber System. We present detailed abundances for as many as 20 elements per star, including 12 elements heavier than the Fe group. We confirm previous detection of high levels of r-process material in Ret 2 (mean [Eu/Fe] = +1.69 ± 0.05) found in three of these stars (mean [Fe/H] = −2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 153 publications
11
130
0
Order By: Relevance
“…Recently, Ji et al (2016a) and Roederer et al (2016) reported the first discovery of highly r-process enriched stars in a UFD, Reticulum II, while there are only strong upper limits on the abundances of r-process elements for some other UFDs (Frebel et al 2010(Frebel et al , 2014Roederer & Kirby 2014). These measurements that show large fluctuations in the r-process abundance imply that only a single r-process event took place in Reticulum II.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Ji et al (2016a) and Roederer et al (2016) reported the first discovery of highly r-process enriched stars in a UFD, Reticulum II, while there are only strong upper limits on the abundances of r-process elements for some other UFDs (Frebel et al 2010(Frebel et al , 2014Roederer & Kirby 2014). These measurements that show large fluctuations in the r-process abundance imply that only a single r-process event took place in Reticulum II.…”
Section: Introductionmentioning
confidence: 98%
“…We do not consider Sagitarius, since this galaxy has been shown to be considerably tidally disrupted (Ibata et al 1995;Mateo et al 1996;Majewski et al 2003), and its mass is therefore very uncertain. Table 1 shows the V-band luminosities, L V , the velocity dispersions, σ, and the half light radii, r 1/2 taken from Walker et al (2009Walker et al ( , 2015, and the average Fe and Eu abundances (Shetrone et al 2001(Shetrone et al , 2003Frebel et al 2010;Letarte et al 2010;Frebel et al 2014;Ji et al 2016a,b;Roederer & Kirby 2014;Tsujimoto et al 2015;Roederer et al 2016). The errors of the average abundances shown in …”
Section: The Galaxy Samplementioning
confidence: 99%
“…Reticulum II: Nine stars in RetII have been analyzed with high-resolution spectroscopy, and seven of these show large enhancements in r-process elements (Ji et al 2016a(Ji et al , 2016bRoederer et al 2016). One of the r-process enhanced stars in RetII also has a high Ba abundance ( Eu Ba 0.3…”
Section: R-process Enhanced Stars In Dwarf Galaxiesmentioning
confidence: 99%
“…In addition to their presence in the halo, a number of rprocess enhanced stars have also been found in dwarf galaxies that are satellites of the MW, highlighted by the discovery that seven of the nine brightest stars in the ultra-faint dwarf ReticulumII (Ret II) are r-II stars (Ji et al 2016a;Roederer et al 2016). Several long-studied dwarfs such as Draco, Ursa Minor (UMi), Sculptor, Fornax, and Carina also contain rprocess enhanced stars (e.g., Shetrone et al 2003;Cohen & Huang 2010;Lemasle et al 2014;Tsujimoto et al 2015), although the implications of these stars have received relatively little attention in the literature.…”
mentioning
confidence: 99%
“…Instead, the approach of determining their kinematics or chemistry still remains valid as a main diagnostic for distinguishing the two types of stellar systems (e.g., see discussions in Belokurov et al 2014;Laevens et al 2014;Kirby et al 2015c;Voggel et al 2016;Weisz et al 2016). Spectroscopic follow-ups for the kinematic and chemical properties are rapidly catching up with the discoveries of the new satellites, but it is a technical challenge to study more than a handful of member stars in these systems due to their intrinsic low total luminosities and therefore lack of bright red giant branch (RGB) stars (Kirby et al 2015a;Koposov et al 2015b;Martin et al 2015Martin et al , 2016aMartin et al , 2016bSimon et al 2015;Walker et al 2015Walker et al , 2016Ji et al 2016;Roederer et al 2016).…”
Section: Introductionmentioning
confidence: 99%